Biocultural determinants of overweight-obesity among adult women experiencing the nutritional transition in the Democratic Republic of Congo - Wakilongo, Wakenge; Abbeddou, Souheila; Vanhoutte, Lucie; Amougou, Norbert; Mubagwa, Muko; Elmira, Clémence; Pasquet, Patrick; Cohen, Emmanuel (Frontiers in Nutrition, 2024)
Introduction The African Great Lakes region is experiencing rapid urbanization, which is leading to a nutritional transition and its related chronic diseases. Similar to other Great Lakes countries, the nutritional transition in the Democratic Republic of Congo (DRC) is reflected by increased non-communicable diseases, including morbid obesity. The 2014 Demographic Health Survey (DHS) revealed a rising incidence of overweight among women, ranging from 10% in 2001 to 16% in 2014. Furthermore, over 20% of individuals in several provinces of the DRC are classified as overweight-obese. This study aimed to investigate the prevalence as well as the main biocultural determinants of overweight-obesity among adult women in the DRC. Methods In a cross-sectional survey, including a representative sample of adult Congolese women living in the South Kivu province, participants were randomly recruited using a two-stage cluster sampling technique after an initial urban–rural stratification. The estimation of the was based on previous results from DHS. Thus, a total of 495 individuals were selected, including 325 urban and 170 rural subjects. Data were collected from households by dietitians who were specifically trained for this survey. Results In this study population, the prevalence of overweight-obesity was 33.6%, with 7.1% classified as obese. The prevalence of obesity was significantly higher among urban people, while all subjects with obesity were from the older age group (>35 years). Using binomial logistic regressions, it was observed that overweight-obesity had a significant positive correlation with the duration of urban residence, namely, Migrants' status: “New residents” 4.6 [1.9–11.7] p < 0.003, “Long term residents” 8.7 [3.5–21.5] p < 0.001; Socio-economic status (SES): “High” 2.4 [1.1–5.3] p < 0.03, and Stoutness valorization: “Yes” 6.1 [3.4–10.9] p < 0.001. In a pathway analysis conducted based on a structural equation model (SEM), we discovered that urban residence and SES were associated with an increase in overweight-obesity, with a positive correlation with processed food consumption and a negative correlation with physical activity. Age was associated with an increase in overweight-obesity through a negative association with physical activity, whereas stoutness valorization directly increased overweight-obesity. Discussion In order to properly guide public health policies, public authorities in the DRC should consider the main findings of this original study, which identify how socio-demographic and socio-ecological factors contribute jointly to the rising prevalence of overweight-obesity in the country.